Reducing convergence time along with improvement in path service quality of border gateway protocol - Agarwal, Arushi; Pandey, Ayushi (International Journal of Engineering and Technology, 2018)
Border Gateway Protocol (BGP) is an exterior gateway routing protocol used between various autonomous systems across the internet. BGP helps in selecting the best route for the transmission of data among the users. The transmission policy followed by BGP should be such that it should increase BGP routing performances. This work aims to reduce the convergence time of the network with the improvement of QOS (Quality of Service) in the routing of Border Gateway Protocol. Our results show that we can obtain a reduced framework environment which has a best routing path with better energy and quality, along with reduction in convergence time.Â